Colonic fermentation of polyphenolics from Sea buckthorn (Hippophae rhamnoides) berries: Assessment of effects on microbial diversity by Principal Component Analysis. (March 2018) - Attri, Sampan; Sharma, Kavita; Raigond, Pinky; Goel, Gunjan
Abstract: The present study investigates the stability of polyphenolic in Sea buckthorn berries juice (SBJ) during different phases of digestion and its effect on colonic microbial diversity. At each stage, the Total polyphenolic content (TPC), Total antioxidant activity (TAA) and polyphenolic profile was determined. A 1.64 and 2.20 folds increase in TPC with 4.88 and 9.61 folds increase in TAA were observed during gastric and small intestine digestion ( p  < 0.05) with the release of quercetin from food matrix. The digestion resulted in deformation of intact crystalline structure as indicated by scanning electron micrographs. The colonic fermentation resulted in an increase in quercetin, caffeic acid with decrease in rutin and chlorogenic acid after 36 h of fermentation ( p  < 0.05). The Shannon diversity index (H) of beneficial groups including Lactic acid bacteria (LAB), Bacteroides/Prevotella and Bifidobacteria was increased by 35%, 71% and 17%, respectively ( p  < 0.05). The PCA analysis indicated that the presence and digestion of polyphenolics promote the proliferation of Bacteroides/Prevotella group as well as Lactic acid bacteria and Bifidobacteria. The results suggest that SBJ is good source of prebiotic substrate in terms of the proliferation of beneficial gut microbiota. Graphical abstract: Highlights: Simulated gastrointestinal conditions release phenolics from berries extract. Rutin and quercetin are the major phenolic in Sea buckthorn berries. Polyphenolics from Sea buckthorn berries promote growth of beneficial bacteria.